2006
DOI: 10.1016/j.adolescence.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The socialization of adolescent coping behaviours: Relationships with families and teachers

Abstract: A motivational theory of children's coping identified aspects of relationships—involvement, structure and autonomy support—that are expected to determine whether coping will be characterized by approach (active) or avoidance. Associations between adolescents’ (, Age ) relationships with families and teachers, and coping behaviours were examined. Whether a Family Primacy Model or a Context‐Specific Model best explained the findings was also determined. A Family Primacy Model received predominant support; adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
1
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 46 publications
(64 reference statements)
5
74
1
12
Order By: Relevance
“…The pairing of these events involving upheaval with having parents who were extremely passive, delinquent in their own behavior, or encouraging of youth delinquent behavior (e.g., social learning theory) seemed to result in youths' delinquency. Other studies have indicated similar results (e.g., Kaplan, 1996;Mack et al, 2007;Zimmer-Gembeck & Locke, 2007), including that of Zimmermann (2006), who confirmed that family structure, particularly that which has been disrupted, was one of the discriminating factors for adolescent boys who engaged in delinquent behaviors.…”
Section: Discussionmentioning
confidence: 50%
“…The pairing of these events involving upheaval with having parents who were extremely passive, delinquent in their own behavior, or encouraging of youth delinquent behavior (e.g., social learning theory) seemed to result in youths' delinquency. Other studies have indicated similar results (e.g., Kaplan, 1996;Mack et al, 2007;Zimmer-Gembeck & Locke, 2007), including that of Zimmermann (2006), who confirmed that family structure, particularly that which has been disrupted, was one of the discriminating factors for adolescent boys who engaged in delinquent behaviors.…”
Section: Discussionmentioning
confidence: 50%
“…The socialization of coping with violence may further explain why shared perspectives are adaptive (Kliewer et al 2006;Power 2004;Zimmer-Gembeck and Locke 2007). According to Kliewer et al (2006) model of coping socialization, children's coping strategies are influenced, in part, by caregiver coaching, or direct suggestions for how to cope with violence.…”
Section: Caregiver Supportmentioning
confidence: 98%
“…Temperament of the child is also a contributing factor to coping, but is dynamic and can be altered (Fox et al 2005;Gunnar and Cheatham 2003;Rutter 1983). Intrapersonal self-regulation begins in toddlerhood, and is scaffolded by significant adults who teach and model how to appraise and confront stressful situations (Power 2004;Zimmer-Gembeck and Locke 2007). Middle childhood brings changes in cognition that allows children to co-ordinate coping strategies with others (Skinner and Zimmer-Gembeck 2007).…”
Section: The Role Of the Family In Adolescent Distress And Copingmentioning
confidence: 98%